ANALISIS DAMPAK WAKTU TANAM TANAMAN TOMAT TERHADAP BIAYA PRODUKSI, HARGA DAN PENDAPATAN USAHATANI DI KECAMATAN ALAS KABUPATEN SUMBAWA - Selfiyah Safitri; Bambang Dipokusumo; Syarif Husni (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2021)
This study aims to examine the differences in the cost structure and income of tomato farming at various planting seasons in Alas Subdistrict, Sumbawa Regency. The data collected is primary data through questionnaires and secondary data, namely data obtained from BPS and scientific papers related to this research. The analysis technique is a survey technique and is presented in tabular form. The results of this study indicate that the average cost spent on tomato farming in the dry season is IDR 75.047.412/ ha, while the cost of tomato farming during the rainy season is IDR 64.273.351/ ha, the average price of tomatoes in the dry season is IDR Rp. 11,790 per kg, while in the rainy season it is Rp. 5,435 per kg and income. In the dry season, income from tomato farming is Rp 150.430.781/ ha, while for the rainy season it is Rp 20.304.842/ ha. This shows that there are significant differences in the costs and income of tomato farming in various planting seasons in Alas District, Sumbawa Regency.